ESTIMATION AND COMPARISON OF INTRA OPERATIVE BLOOD LOSS IN PATIENTS WITH AND WITHOUT VENOUS THROMBOEMBOLISM PROPHYLAXIS: Intra Operative Blood Loss - Ahsin, Sadia; Bashir, Etizaz Ahmed; Faiz, Syed Abdullah; Tahir, Junaid; Ijaz, Aashir (Pakistan Armed Forces Medical Journal, 2014)
Objective: To estimate and compare intraoperative blood loss in surgical patients with and without deep vein thrombosis (DVT) prophylaxis using unfractionated heparinStudy Design: Clinical TrialPlace and Duration: Surgery Department of Fauji Foundation Hospital and Physiology Department Foundation University Medical College from October 2011 to August 2012Patients and Methodology: Patients were selected by non probability purposive sampling. Patients fulfilling the inclusion criteria were divided into 2 groups 25 each on the basis of order of presentation at Fauji Foundation Hospital until cohort numbers were reached. Group I received no heparin whereas group II received heparin. Written informed consent was taken from the patient after explaining the procedure of the study. Coagulation profile was done for both groups before the planned surgery. Heparin in a dose of 5000 units was administered subcutaneously to group II on the morning of the planned surgery and it was stopped 24 hours post operatively. Blood loss was estimated in both groups by weighing cotton swabs pre and post operatively. Data was analyzed by SPSS version 17.Results: Demographic data and surgical procedure time between the two groups did not differ. Blood loss between the two groups did not show any statistically significant difference.Conclusion: DVT prophylaxis using unfractionated heparin did not lead to any significant overt blood loss when compared with those without it.